Factors associated with the initiation of laxative use in the same patients with schizophrenia over a 20‐year period: Retrospective cohort study - Yasushi Kawamata; Norio Sugawara; Taro Sasaki; Saaya Yokoyama; Hiroaki Okayasu; Masataka Shinozaki; Yoshitaka Takeuchi; Aoi Sato; Takaaki Ishikawa; Hazuki Komahashi‐Sasaki; Kensuke Miyazaki; Takashi Fukasawa; et al. (Neuropsychopharmacology Reports, 2024)
Abstract Background Constipation is a common adverse effect of antipsychotics, but little investigation has been conducted. We aimed to address the factors associated with the initiation of laxative use in the same patients with schizophrenia over a 20‐year period. Methods We enrolled patients with schizophrenia attending each hospital (n = 14) from April 1, 2021, and retrospectively examined all prescriptions as of April 1, 2016, 2011, 2006, and 2001, every 5 years starting in 2021, for this population. 716 participants with complete data were included in the analysis. The Cochran Q test followed by Bonferroni correction and the Cochran–Armitage trend test were used to determine the differences and trends of the frequency of each laxative. Multivariate logistic regression analysis was performed to assess the factors on the initiation of laxative use over a 20‐year period. Results Of the patients, 25.1% were treated with laxatives in 2001, and 34.1% were treated in 2021. The numbers of patients treated with any laxatives significantly differed over the 20‐year period, with a significant increasing trend. In all laxatives, the numbers of patients treated with magnesium oxide, lubiprostone and elobixibat differed with a significant increasing trend. Female sex, age, the total DZP equivalent dose, and the doses of levomepromazine maleate, olanzapine, quetiapine, zotepine, lithium, and carbamazepine in 2021 were significant factors associated with the initiation of laxative use over the 20‐year period. Conclusions Careful monitoring is needed for patients treated with levomepromazine maleate, olanzapine, quetiapine and zotepine. Optimizing prescriptions according to treatment guidelines could reduce antipsychotic‐induced constipation.